Customer Capital - Gourio, F.; Rudanko, L. (Review of Economic Studies, 2014)
Firms spend substantial resources on marketing and selling. Interpreting this as evidence of frictions in product markets, which require firms to spend resources on customer acquisition, this article develops a search theoretic model of firm dynamics in frictional product markets. Introducing search frictions generates long-term customer relationships, rendering the customer base a state variable for firms, which is sluggish to adjust. This affects: the level and volatility of firm investment, profits, value, sales and markups, the timing of firm responses to shocks, and the relationship between investment and Tobin's q. We document support for these predictions in firm-level data from Compustat, using cross-industry variation in selling expenses to quantify differences in the degree of friction across markets.